A BIT OF BITING: PHOTOGRAPHY. (February 2015) - Forrest, Alex
Abstract : Photography plays a vital role in bite mark analysis and comparison, and is equally important to the analysis of other patterned injuries. Accurate representation of injuries in acquired images without introduced distortion forms the basis for scaling and measurement, and underlies all comparison techniques. Sources of introduced image errors are discussed and methods are shown to correct these (when correction is possible), or to avoid them at the time of photography. The outcomes and consequences of inappropriate image corrections are also illustrated.